2015
DOI: 10.4238/2015.august.19.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of sweet kernel apricot in China based on SSR and ISSR markers

Abstract: ABSTRACT. Simple sequence repeat (SSR) and inter-simple sequence repeat (ISSR) markers were used to evaluate genetic diversity among 22 sweet kernel apricot accessions and 12 cultivars in China to provide information on how to improve the utilization of kernel apricot germplasms. The results showed that 10 pairs of SSR primers screened from 40 primer pairs amplified 43 allelic variants, all of which were polymorphic (100%), and 9 ISSR primers selected from 100 primers amplified 67 allelic variants with 50 poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…The data also allow the identification of unknown cultivars and cases of synonyms. Our results were also in agreement with Liu et al (2015) who used ISSR markers to evaluate genetic diversity among 22 sweet kernel apricot accessions and 12 cultivars in China to provide information on how to improve the utilization of kernel apricot germplasms. The results showed that 9 ISSR primers amplified 67 allelic variants with 50 polymorphic bands (74.63%).…”
Section: Consensus Tree According To Issr Banding Patternssupporting
confidence: 90%
See 1 more Smart Citation
“…The data also allow the identification of unknown cultivars and cases of synonyms. Our results were also in agreement with Liu et al (2015) who used ISSR markers to evaluate genetic diversity among 22 sweet kernel apricot accessions and 12 cultivars in China to provide information on how to improve the utilization of kernel apricot germplasms. The results showed that 9 ISSR primers amplified 67 allelic variants with 50 polymorphic bands (74.63%).…”
Section: Consensus Tree According To Issr Banding Patternssupporting
confidence: 90%
“…The results showed that ISSR technique was suitable for genetic diversity analyses and the identification of pecan resources. Liu et al (2015) used inter-simple sequence repeat (ISSR) markers to evaluate genetic diversity among 22 sweet kernel apricot accessions and 12 cultivars in China. They reported that the nine used ISSR primers amplified 67 allelic variants with 50 polymorphic bands (74.63%).…”
mentioning
confidence: 99%
“…However, the contribution of the various wild Prunus species to the current Chinese cultivated germplasm has been little studied, or with insufficient sample sizes so far (Ai, Zhen, & Jin, 2011;Geuna, Toschi, & Bassi, 2003;Zhebentyayeva et al, 2008). Moreover, previous studies on the genetic diversity of Chinese species focused separately on cultivated (Li, Zhao, & Miao, 2014;Li et al, 2010;Liu, Du, Zhu, Fu, & Tana, 2015;Zhang et al, 2014) or wild apricots (He et al, 2007;Li, Zhao, Miao, & Zhou, 2013;Wang et al, 2014), without inferences on Chinese apricot domestication history.…”
mentioning
confidence: 99%
“…ansu have primarily been based on phenotypic traits [ 4 , 14 ], but the morphological indexes are susceptible to environmental influences. With the rapid development and improvement of molecular biology techniques, AFLP [ 15 ], RAPD [ 16 ], SRAP [ 17 ], ISSR [ 18 ] and SSR have all been widely deployed in germplasm evaluation [ 19 ], genetic map construction [ 15 ], genetic diversity assessment [ 20 ], genetic relationship analysis [ 13 ], and population structure analysis [ 21 ] in the genus Prunus Mill. Germplasm provides important resources for exploring and protecting the genetic and phenotypic diversity of breeding applications.…”
Section: Introductionmentioning
confidence: 99%